2014
DOI: 10.14740/jcs236w
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gender, Age and BMI on Postoperative C-Reactive Protein Levels After Major Abdominal Surgery

Abstract: Background: The aim of this observational study was to analyze whether differences exist in postoperative C-reactive protein (CRP) levels in elderly, obese or for gender after major abdominal surgery, which might affect the diagnostic value of CRP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Previous research has indicated that patient factors such as sex, age, and BMI, have a negligible effect on postoperative CRP levels. 34 In addition, the present results indicate that surgical indication, smoking status, or additional HIPEC did not significantly influence CRP levels. Conversely, combining CRP with other markers, such as intestinal fatty acid binding protein and interleukin-6, might increase its diagnostic value.…”
Section: Discussionsupporting
confidence: 43%
“…Previous research has indicated that patient factors such as sex, age, and BMI, have a negligible effect on postoperative CRP levels. 34 In addition, the present results indicate that surgical indication, smoking status, or additional HIPEC did not significantly influence CRP levels. Conversely, combining CRP with other markers, such as intestinal fatty acid binding protein and interleukin-6, might increase its diagnostic value.…”
Section: Discussionsupporting
confidence: 43%
“…In uneventful cases, the levels decrease after this peak [ 24 ]. Furthermore, the plasma half-life of CRP is 19 hours and postoperative CRP levels are independent of gender, age, body mass index (BMI), diet, diurnal rhythm or organ function [ 25 ]. Circulating CRP levels are therefore only determined by their rate of synthesis [ 26 ].…”
Section: Introductionmentioning
confidence: 99%